Offshore oil exploitation in the Caribbean Sea: Challenges for Colombia (2020)
Colombia began an expansion plan for oil exploration in the Caribbean Sea, this industry is recognized for the high impact it can generate, being necessary to identify mechanisms to improve management. This research presents a review of the experiences in the offshore oil industry, describes the case of oil exploration in the Arctic, a fragile ecosystem; methodologies and indicators used to strengthen the industry in order to achieve sustainability are identified. The results allow to conclude that it is necessary to strengthen the development plan from the institutional and political frameworks using a Strategic Environmental Assessment, also they indicate how this can improve the instruments and achieve improvement in the social, economic and environmental dimensions.